Induction of oral tolerance in mice unresponsive to bacterial lipopolysaccharide. - Saklayen, M G (1983)
C3H/HeJ lipopolysaccharide (LPS)-unresponsive and closely related C3H/HeSn LPS-responsive mice were rendered tolerant to hen albumin by antigen feeding before parenteral immunization. Both single and multiple feedings of antigen were effective in inducing tolerance to hen albumin in LPS-responsive and -unresponsive strains of mice. Our data demonstrate that ability to respond to LPS is not a prerequisite for induction of oral tolerance to a soluble protein antigen.